(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Adolescent pregnancy is a global health issue that affects millions of young girls and their families. According to the World Health Organization, approximately 16 million adolescents aged 15-19 years give birth annually, representing 11% of all births worldwide. Most of these pregnancies occur in low- and middle-income countries (LMIC), especially in Sub-Saharan Africa. The burden of adolescent pregnancy in Kenya is 15% of girls aged 15-19 years, with 2.7 % of adolescents aged 15 years having ever been pregnant. Unintended pregnancies among adolescents in Kenya account for most maternal morbidity and mortality cases from abortions. Pregnant adolescents are at an increased risk of pregnancy and childbirth complications, unsafe abortion, violence from intimate partners, HIV/AIDS, and other sexually transmitted infections. Furthermore, infants born to adolescent mothers have higher probability of mortality and exposure to life-threatening conditions. This policy brief reviews and analyses the factors associated with unintended adolescent pregnancies in Kenya and identifies evidence-based interventions that can be applied in the local context. It argues that a multisectoral approach involving education, contraception, and incentives is needed to address adolescent pregnancies. In conclusion, more research is needed to tailor these interventions to the local Kenyan context while analyzing the availability and mobilization of resources.